IMPLEMENTASI STRATEGI ISLAMIC MARKETING MIX PADA KOKUMI TRANSMART RUNGKUT SURABAYA - Nurfaizah, Fatima Carmitha (Jurnal Ekonomika dan Bisnis Islam, 2021)
Wide competition causes the need for a marketing strategy that can make its business grow, one of which is the 4P marketing mix (product, price, place, and promotion) as a marketing tool, which will then have an influence on the sales volume owned by the company. The focus of this research is the implementation of the 4P marketing mix strategy at Kokumi Transmart Surabaya which is associated with conformity based on sharia principles. This type of research uses field research, in which to obtain data using interviews, observation, and documentation. This understanding uses a qualitative approach. The conclusions in this study indicate that the implementation of the marketing mix carried out by Kokumi Transmart Rungkut is in accordance with Islamic principles and principles, as evidenced by the condition of the product which does not contain intoxicating elements for consumers and also does not contain pork, for pricing Kokumi provides competitive prices and adjusts From the quality level given, promotional activities are also carried out well, there is no act of cheating or even trying to overthrow other competitors, and in organizing the venue, Kokumi has provided a comfortable and safe place for its consumers.